2019
DOI: 10.1111/bjh.16156
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 contributes to hepatic hepcidin (HAMP) inhibition through SMURF1‐mediated BMP‐SMAD signalling suppression

Abstract: Hepcidin (HAMP) synthesis is suppressed by erythropoiesis to increase iron availability for red blood cell production. This effect is thought to result from factors secreted by erythroid precursors. Growth differentiation factor 11 (GDF11) expression was recently shown to increase in erythroid cells of b-thalassaemia, and decrease with improvement in anaemia. Whether GDF11 regulates hepatic HAMP production has never been experimentally studied. Here, we explore GDF11 function during erythropoiesistriggered HAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…The new therapeutic luspatercept, which acts as a trap ligand to inactivate GDF11, has been shown to increase RBC count and hematocrit in healthy and anemic individuals [ 132 , 133 ]. While it has been demonstrated that GDF11 can inhibit hepcidin levels, thereby connecting erythropoiesis to iron metabolism, other studies have questioned the role of GDF11, since the murine homolog of luspatercept, RAP-536, also enhanced erythropoiesis in GDF11 KO mice [ 134 , 135 ]. Therefore, further studies are needed to investigate the role of GDF11 in human erythropoiesis and iron regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The new therapeutic luspatercept, which acts as a trap ligand to inactivate GDF11, has been shown to increase RBC count and hematocrit in healthy and anemic individuals [ 132 , 133 ]. While it has been demonstrated that GDF11 can inhibit hepcidin levels, thereby connecting erythropoiesis to iron metabolism, other studies have questioned the role of GDF11, since the murine homolog of luspatercept, RAP-536, also enhanced erythropoiesis in GDF11 KO mice [ 134 , 135 ]. Therefore, further studies are needed to investigate the role of GDF11 in human erythropoiesis and iron regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin binds to ferroportin on enterocytes and iron-storing cells like macrophages, resulting in an internalization and degradation of the hepcidin-ferroportin complex and thus effectively shuts down nutritional iron absorption and iron release from internal iron storage. Hepcidin expression is controlled by regulatory feedback mechanisms that involve active erythropoiesis: erythroblast-derived erythroferrone (ERFE), growth differentiation factor 11 (GDF11), growth differentiation factor 15 (GDF15) and twisted gastrulation protein homolog 1 (TWSG1) have been shown to influence hepatic hepcidin secretion, thus linking erythropoietic iron demand to iron supply (15)(16)(17)(18).…”
Section: Iron Homeostasis and Its Role For Normal Hematopoiesismentioning
confidence: 99%
“…MitoTEMPO, a mitochondrion-targeted ROS inhibitor, inhibits the GDF11-induced activation of c-Jun amino-terminal kinase and adenosine monophosphate-activated protein kinase; thus, the GDF11-induced activation of c-Jun amino-terminal kinase and adenosine monophosphate-activated protein kinase can be modified by ROS status [ 37 ]. Recently, ERK1/2 signaling was found to be activated by GDF11, which downregulated bone morphogenetic protein–SMAD signaling and hepcidin activity [ 38 ].…”
Section: Gdf11 Signaling Pathwaymentioning
confidence: 99%